Correction: Structural and functional features of medium spiny neurons in the BACHDΔN17 mouse model of Huntington's Disease. - Joseph Goodliffe; Anastasia Rubakovic; Wayne Chang; Dhruba Pathak; Jennifer Luebke (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0234394.].